(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Big data is not just a large data in amount but it is also growing exponentially with time. Big data is based on the concept of 3 Vs i.e. Volume, Velocity & Variety. As specified in definition it is huge in terms of Volume & new data is received at fast rate. The big data is also available in various format. This data need not be structured, but at times it is semi structured or unstructured. This type of data also needs processing to make it useful. They are so voluminous that traditional data processing software just can’t manage such huge data. To put simply, Big data contains greater variety, arrives in increasing volumes and is ever-changing frequently.